THE EFFECT OF CORPORATE IMAGE AND SERVICE QUALITY TO INTENTION TO MOVE THROUGH SATISFACTION IN MEMBER RAI FITNESS IN SAMARINDA CITY - Aditya Pratama; Syarifah Hudayah; Gusti Noorlitaria Achmad (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2020)
This study aims to analyze the influence of Company Image and Service Quality on Intentions to Move Through Satisfaction to Rai Fitness Members in Samarinda City. This research uses quantitative by using path analysis obtained with SPSS statistical software version 22.0 and Structural Equation Modeling (SEM) PLS (partial at least aquares). Samples taken in this study were 90 respondents distributed in Samarinda City, they are users Rai Fitness services in Samarinda city, the measurement uses a Likert scale with a score of 1-5. In this study also tested the validity and reliability test, then the estimation test and the model fit structural test were conducted. Based on the structural model we found, Company Image, Service Quality has a significant effect on Customer Satisfaction and a significant negative effect on Intentions to Move.